Effects of graphene oxides on the cure behaviors of a tetrafunctional epoxy resin (eXPRESS Polymer Letters, 2011)
The influence of graphene oxides (GOs) on the cure behavior and thermal stability of a tetrafunctional tetraglycidyl-4,4’-diaminodiphenylmethane cured with 4,4’-diaminodiphenylsulfone was investigated by using dynamic differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The dynamic DSC results showed that the initial reaction temperature and exothermal peak temperature decreased with the increase of GO contents. Furthermore, the addition of GO increased the enthalpy of epoxy cure reaction. Results from activation energy method showed that activation energies of GO/epoxy nanocomposites greatly decreased with the GO content in the latter stage, indicating that GOs significantly hindered the occurrence of vitrification. The oxygen functionalities, such as hydroxyl and carboxyl groups, on the surface of GOs acted as catalysts and facilitated the curing reaction and the catalytic effect increased with the GO contents. TGA results revealed that the addition of GOs decreased the thermal stability of epoxy.